Fabrication and characterization of red-emitting electroluminescent devices based on thiol-stabilized semiconductor nanocrystals - Bertoni, Cristina; Gallardo, Diego E.; Dunn, Steve; Gaponik, Nikolai; Eychmüller, Alexander (American Institute of Physics (AIP), 2007)
Thiol-capped CdTe nanocrystals were used to fabricate light-emitting diodes, consisting of an emissive nanocrystal multilayer deposited via layer-by-layer, sandwiched between indium-tin-oxide and aluminum electrodes. The emissive and electrical properties of devices with different numbers of nanocrystal layers were studied. The improved structural homogeneity of the nanocrystal multilayer allowed for stable and repeatable current- and electroluminescence-voltage characteristics. These indicate that both current and electroluminescence are electric-field dependent. Devices were operated under ambient conditions and a clear red-light was detected. The best-performing device shows a peak external efficiency of 0.51% and was measured at 0.35mA/cm2 and 3.3V.